1986
DOI: 10.1161/01.cir.74.5.939
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of platelet aggregability by moderate-intensity physical exercise: a randomized clinical trial in overweight men.

Abstract: It has been postulated that platelet function plays an important role in the initiation of atherosclerosis. Currently there are no definitive data on the longer-term effects of regular physical exercise on platelet function in humans. We assessed the influence of regular moderate-intensity physical exercise (brisk walking to slow jogging) on platelet aggregation in a population-based sample of middle-aged, overweight, mildly hypertensive men in eastern Finland. In this controlled study, we evaluated the net ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(70 citation statements)
references
References 18 publications
3
65
0
2
Order By: Relevance
“…Benefits to the circulatory system include influences on the lipoprotein metabolism, inflammatory markers, endothelial function and insulin resistance. [39][40][41][42][43][44][45][46] Is physical activity important among those who lose weight? Our study showed that leisure time physical activity had protective effect on all-cause mortality, which is in line with numerous other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits to the circulatory system include influences on the lipoprotein metabolism, inflammatory markers, endothelial function and insulin resistance. [39][40][41][42][43][44][45][46] Is physical activity important among those who lose weight? Our study showed that leisure time physical activity had protective effect on all-cause mortality, which is in line with numerous other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise has been reported by our group to be protective against development of the disease. ** There are many beneficial effects of physical activity that may be related to reduced risk of AD: lower body weight, improved diet (including increased consumption of antioxidants and lower fat intake), improved blood pressure and cardiovascular health, as well as beneficial effects on blood clotting (25).…”
Section: Discussionmentioning
confidence: 99%
“…Other potential benefits of such activity, which may aid in the prevention of and recovery from cardiovascular disease include increased glucose tolerance and decreased insulin sensitivity 50 , reduction in platelet aggregation 51 and plasma fibrinogenesis 52 . Such functional adaptations often fulfill a more important role than traditional risk factors proper and should, therefore, be considered in the analysis of the advantages of the regular practice of physical activity in terms of the reduction in the incidence of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%